Strategic Customer Service Innovation on Organizational Success of Elderly Care Business in Thailand - Wimonchailerk, Thanwaporn (Interdisciplinary Academic and Research Journal, 2023)
Strategic Customer Service Innovation is a service to support the use of products or services. Service innovations tend to focus on ICT as part of the service system that provides convenience and saves time to customers, as well as providing useful information and value to customers, services are offered through web technologies, and the expected result is to increase business productivity and create a positive customer experience. Thus, the objectives of this research were 1) to study the strategic customer service innovation of the elderly care business in Thailand, 2) to study the organizational success of the elderly care business in Thailand, and 3) to test the relationship between the strategic customer service innovation and 4) to test the impact of strategic customer service innovation on the organizational success of elderly care businesses in Thailand. Implement concepts of strategic customer service innovation and corporate success. The data were collected from 118 elderly care business operators in Thailand. The questionnaire was used as a tool. Statistics used in data analysis were percentage, mean, and standard deviation. Multiple correlation analysis simple regression analysis and multiple regression analysis. (1) The results of the research revealed that entrepreneurs in the elderly care business in Thailand Also commented on strategic customer service innovation. overall and side by side at the highest level, including maintaining a sustainable relationship Customer Satisfaction, and value creation for customers and elderly care business operators in Thailand Have opinions about the success of the organization. overall and side by side at the highest level, namely financial aspects, customer aspects, internal processes, and learning and development. (2) The relationship and impact analysis, it was found that 1) Strategic customer service innovation Sustainable relationship maintenance 2) Strategic customer service innovation Customer Satisfaction It has a positive relationship and impact on the success of the organization, financial, customer, internal processes. and learning and development. 3) Strategic customer service innovation. Value creation for customers It has a positive relationship and impact on the success of the organization, finances, and internal processes.